Paradigma Baru Hukum Acara Pidana: Rekonstruksi Perlindungan Hak Asasi Tersangka dalam Proses Peradilan - M. Supian Noor; Akhmad Munawar; Lutfi Yusup Rahmathoni (CV Rewang Rencang, 2024)
The Indonesian criminal justice system faces significant challenges in balancing legal certainty and the protection of suspects' human rights. Although the presumption of innocence principle is enshrined in various laws and regulations, pretrial detention practices are often misused by law enforcement officials as a psychological pressure tool against suspects. Article 21 of the Indonesian Criminal Procedure Code (KUHAP) grants broad discretionary powers to investigators and prosecutors in determining detention, without stringent judicial oversight. This situation creates a high risk of arbitrary criminalization, which contradicts the fair trial principle as stipulated in the International Covenant on Civil and Political Rights (ICCPR). This article analyzes the fundamental weaknesses in the criminal procedural law system, particularly in detention mechanisms and pretrial judicial oversight, and proposes a more just and accountable system reconstruction. KUHAP reform is necessary to establish stricter minimum evidence standards before detention, expand pretrial judges' authority to assess the substance of evidence, and strengthen independent oversight of detention decisions made by law enforcement officials. By implementing these reforms, Indonesia's criminal justice system can become more transparent, accountable, and aligned with internationally recognized human rights protection principles.